Mefloquine is highly efficacious against chloroquine-resistant Plasmodium vivax malaria and Plasmodium falciparum malaria in Papua, Indonesia. - Maguire, J; Krisin; Marwoto, H; Richie, T; Fryauff, D; Baird, J (2006)
BACKGROUND: During the period of 1996-1999, we prospectively monitored 243 Javanese adults and children after arriving in Papua, Indonesia, and microscopically documented each new case of malaria by active surveillance. METHODS: In a randomized, open-label, comparative malaria treatment trial, 72 adults and 50 children received chloroquine for each incident case of malaria, and 74 adults and 47 children received mefloquine. RESULTS: Among 975 primary treatment courses, the cumulative 28-day curative efficacies were 26% and 82% for chloroquine against Plasmodium falciparum malaria and Plasmodium vivax malaria, respectively. Mefloquine cure rates were far superior (96% against P. falciparum malaria and 99.6% against P. vivax malaria). CONCLUSIONS: Mefloquine is a useful alternative treatment for P. vivax malaria and P. falciparum malaria in areas such as Papua, where chloroquine is still recommended as the first-line therapeutic agent.